El verbo francés en la terminología culinaria. Análisis lexicográfico. Equivalencias con el español - Marcos García, María Josefa (Anales de Filología Francesa, 2010)
The culinary terminology does not constitute a language reserved for the specialists. The cooking is an activity practised in a daily way in all the homes and this type of vocabulary is a member, often, of the common language. It is for it that we want to verify what is the presence of this type of terms in the general dictionaries. We elaborated French- Spanish bilingual corpus to realize a contrastive analysis. In this corpus we selected the verbs .We have analyzed the presence or the absence of these verbs in the analyzed dictionaries, the Thematic marks and some aspects of the definition. Finally, we established, a glossary with the French-Spanish equivalences.